Ecological Potency and Utilization of Sea Cucumber In Seagrass Ecosystem at Tatumbu Island West Seram - Yona A. Lewerissa; Prulley A. Uneputty; Tejo Sugiantoro (Sangia Publishing, 2021)
Holothurians have benefit both for economic and ecology. Economically, holothurians are source for protein and could be used for healing some diseases. Therefore, they have highly expensive both local and international scale. In addition, ecologically they are source for food and substrate fertilizer. Tatumbu Island is uninhabitant in Kotania Bay, West Seram and coverage by seagrass ecosystem. So, it would be suitable place for holothurians distribution. Nowadays, the demands for holothurians are still highly for export commodity. Consequently, the population would decrease in the future. The purpose of this study is to know the densit, potential and the utilization of holothurians in Tatumbu Island. Data were collected at three stations by using Belt Transect. To identify the utilization of holothurians, the interview was done by using questionnaire. Environmental parameters were measured in situ including temperature, salinity and potential of hydrogen (pH). The results showed that there were nine commercial species and other three species found. The density of three stations ranged from 0,0012-0,0353 ind.m-2 and the potential was 17187 individuals. The highest density and potential were represented by Stichopus horrens whilst the lowest density was represented by Actinopyga echinites. Generally, holothurians distribution on sandy substrate associated with seagrass. The utilization of holothurians is conducted daily and continues by fishers. The temperature, salinity and pH indicated that the waters of Tatumbu Island were suitable for sea cucumber growth.